2018
DOI: 10.4149/bll_2018_102
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of epicardial fat tissue thickness with oxidant biomarkers in chronic kidney disease

Abstract: We believe that we have introduced three novel follow-up parameters, such as: IMA, MPO, EFTT to literature for the follow-up of CKD. As the levels of IMA MPO and EFTT increase, the severity of CKD increases (Tab. 4, Fig. 1, Ref. 25).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…Many studies have proposed an association of CKD with epicardial fat thickness (EFT). Previously increased EFT has been noted in hemodialysis patients [10].…”
Section: Introductionmentioning
confidence: 92%
“…Many studies have proposed an association of CKD with epicardial fat thickness (EFT). Previously increased EFT has been noted in hemodialysis patients [10].…”
Section: Introductionmentioning
confidence: 92%
“…In a study carried out in a cohort of more than 400 patients with CKD stage 4-5 and 5 on dialysis EF emerged as a risk factor for alterations in myocardial perfusion as well as appearance of vascular calcification ( 3 ), and was also independently associated with vascular calcification in predicting myocardial perfusion defects in this study. Karatas et al recently demonstrated that EAT thickness measured by echocardiography was significantly greater in hemodialysis patients than in those in pre-dialysis stages or in healthy subjects ( 47 ). Similarly, in a sub analysis of the RIND study (Renagel in a new dialysis trial), which initially evaluated the presence of coronary artery calcifications (CAC) and alterations in calcium and phosphorus in patients starting dialysis treatment, it was observed that each 10 cc increase in EF volume raised mortality by 6% ( 4 ).…”
Section: Organ-specific Fat As Causative Factor Of Cardiorenal Diseasementioning
confidence: 99%
“…Several studies have demonstrated that the EAT thickness is high in hemodialysis or peritoneal dialysis patients than the healthy subjects (see Table 2 [47,48,49,50,51,52,53]). In a study by Sheng et al n 120 patients with CKD and 30 healthy subjects, cardiac CT showed higher EAT volume in stage 4–5 D CKD group patients compared with the control group; however, EAT volume was similar between CKD 3 and control group [54].…”
Section: Eat In Chronic Kidney Disease (Ckd) and End-stage Renal Dmentioning
confidence: 99%
“…PON-1 is the most potent high-density lipoprotein (HDL) associated antioxidant enzyme whose activity has been demonstrated to be inversely correlated with oxidative stress and cardiovascular risk [56,57]. Apart from this, a strong correlation was observed between EAT thickness and ischemiamodified albumin (IMA) and myeloperoxidase (MPO) in hemodialysis patients; IMA is elevated in ESRD, MPO plays a role in inflammation and CVD [49]. An inverse correlation between EAT thickness and coenzyme Q10 levels was observed in hemodialysis patients as compared to matched healthy subjects in a study by Macunluoglu et al ( p < 0.05) [58].…”
Section: Eat In Chronic Kidney Disease (Ckd) and End-stage Renal Dmentioning
confidence: 99%